Joint QTL mapping and transcriptome sequencing analysis reveal candidate flowering time genes in Brassica napus L - Hongju Jian; Aoxiang Zhang; Jinqi Ma; Tengyue Wang; Bo Yang; Lan Shuan Shuang; Min Liu; Jiana Li; Xinfu Xu; Andrew H. Paterson; Liezhao Liu (BMC Genomics, 2019)
Abstract Background Optimum flowering time is a key agronomic trait in Brassica napus. To investigate the genetic architecture and genetic regulation of flowering time in this important crop, we conducted quantitative trait loci (QTL) analysis of flowering time in a recombinant inbred line (RIL) population, including lines with extreme differences in flowering time, in six environments, along with RNA-Seq analysis. Results We detected 27 QTLs distributed on eight chromosomes among six environments, including one major QTL on chromosome C02 that explained 11–25% of the phenotypic variation and was stably detected in all six environments. RNA-Seq analysis revealed 105 flowering time-related differentially expressed genes (DEGs) that play roles in the circadian clock/photoperiod, autonomous pathway, and hormone and vernalization pathways. We focused on DEGs related to the regulation of flowering time, especially DEGs in QTL regions. Conclusions We identified 45 flowering time-related genes in these QTL regions, eight of which are DEGs, including key flowering time genes PSEUDO RESPONSE REGULATOR 7 (PRR7) and FY (located in a major QTL region on C02). These findings provide insights into the genetic architecture of flowering time in B. napus.